(untitled) (Economic and Political Thought, 2023)
The article is a development of the work: D. Kotlewski, Oszacowanie wpływu rozwoju infrastruktury na wzrost gospodarczy w świetle rachunku produktywności KLEMS, “Myśl Ekonomiczna i Polityczna” 2022, No. 3(74), in which the dilemmas of infrastructure development are presented and discussed, and the application of KLEMS productivity accounting to the quantitative study of this issue is proposed. The mentioned work is developed by making the relevant calculations within this accounting also at the Polish voievodeship level, rather than only at the aggregate level of the economy. The results are accompanied by a commentary which, among other things, points out that the productive effects of capital engaged in development can now be studied in this way.